FAKTOR-FAKTOR YANG BERPENGARUH PADA VOLUNTARY AUDITOR SWITCHING - Agiastuti, Ida Ayu Putu; Dharma Suputra, I Dewa Gede (E-Jurnal Akuntansi, 2016)
This study aimed to examine the effect of financial distress, the going concern opinion, management changes, and the reputation of KAP on voluntary auditor switching because the results of previous studies showed inconsistent results. Sources of data in this study is a secondary data source that the company's financial statements of property and realestate. This study used a sample of property and realestate company listed on the Indonesia Stock Exchange during the period 2009-2013 are accessible through www.idx.co.id. Number of company property and realestate sampled this study is 22 companies with over 5 years of observation. Determination of the sample using purposive sampling method, the total sample was 110 financial statements. Testing hypotheses used in this research is the logistic regression analysis. The results showed that the variables of financial distress, the going concern opinion, management changes, and reputation KAP positive effect on voluntary switching auditors.
Keywords: Financial distress; going concern opinion; management changes; KAP' s reputation; voluntary auditor switching